Do members of the public think they should use lateral flow tests (LFT) or polymerase chain reaction (PCR) tests when they have COVID-19-like symptoms? The COVID-19 Rapid Survey of Adherence to Interventions and Responses study. (September 2021) - Smith, L.E.; Potts, H.W.W.; Amlȏt, R.; Fear, N.T.; Michie, S.; Rubin, G.J.
Abstract: Objectives: This study aimed to investigate public use of lateral flow tests (LFT) and polymerase chain reaction (PCR) tests when experiencing key COVID-19 symptoms. Study design: In this study, data from two waves of a cross-sectional nationally representative online survey (data collected 1 and 2 June, and 14 and 15 June 2021; n = 3665 adults aged ≥18 years living in England or Scotland) were used. Methods: We report data investigating which type of test, if any, the public think Government guidance asks people to use if they have COVID-19 symptoms. In people with key COVID-19 symptoms (high temperature / fever; new, continuous cough; loss of sense of smell; loss of taste), we also describe the uptake of testing, if any. Results: Ten percent of respondents thought Government guidance stated that they should take an LFT if symptomatic, whereas 18% of people thought that they should take a PCR test; 60% of people thought they should take both types of test (12% did not select either option). In people who were symptomatic, 32% reported taking a test to confirm whether they had COVID-19. Of these, 53% reported taking a PCR test and 44% reported taking an LFT. Conclusions: Despite Government guidance stating that anyone with key COVID-19 symptoms should complete a PCR test, a significant percentage of the population use LFT tests when symptomatic. Communications should emphasise the superiority of, and need for, PCR tests in people with symptoms.